Experimental and numerical analysis of a packed-bed thermal energy storage system designed to recover high temperature waste heat: an industrial scale up. (December 2020) - Touzo, Aubin; Olives, Régis; Dejean, Guilhem; Pham Minh, Doan; El Hafi, Mouna; Hoffmann, Jean-François; Py, Xavier
Highlights: A containerized packed bed thermal storage of 28 tons (1.9 MWhTh ) is investigated. Experimental data for single blow and 3 cycles above 500°C at 300 kWTh are provided. Performances indicators specific to open waste heat recovery systems are given. No channeling and moderate radial thermal gradient were observed. Edge effects are considered to model this industrial plug and play thermal storage. Abstract: An industrial-scale air-ceramic horizontal packed-bed thermal energy storage (Eco-Stock®) has been designed and built by Eco-Tech Ceram and tested during an experimental campaign of 500h. The goal is to provide experimental data and analysis of a horizontal and containerized packed bed TES at high temperature, with performance indicators specific to waste heat recovery. A single charge-discharge at 525°C and 3 cycles at 500°C were carried out (300 kWTh for charge, 350 kWTh for discharge). The unit was able to store up to 1.9 MWhTh in a TES system (1.7 × 1.7 × 3.08 m 3 ) composed by 16-ton of bauxite ceramic media. The packed bed was able to valorize up to 90% of the heat source, which demonstrates the system ability to recover waste heat up to 525°C at industrial scale. No channeling effect and moderate radial thermal gradient were detected, even though the tank had a horizontal geometry. The plug and play TES presents a non-negligible part of its energy stored in the insulant, which can be recovered during discharge. To take into account such phenomenon, a one-dimension 3 temperature model is proposed. The model fitted well with experimental results, with a root mean standard deviation of the model below 20°C for the temperature profiles.